Legal Philosophy Perspectives on Abortion Regulation in Indonesia - Yuwono Prianto; Hanivah Fitriyani; Jessica Sandini; Keiko Patricia Liwe (Universitas Islam Negeri Alauddin Makassar, 2026)
Abortion in Indonesia is a complex legal issue involving moral, religious, and human rights dimensions. Regulations in the Criminal Code, Health Law, and Government Regulation No. 61 of 2014 demonstrate tension between protecting the right to life of the fetus and respecting women's rights to bodily autonomy and reproductive health. This research analyzes abortion regulations from legal philosophy perspectives—natural law, legal positivism, and progressive law—and assesses the extent to which regulations reflect substantive justice. The method employed is normative legal research with statutory, conceptual, and theoretical approaches. Research findings indicate that natural law emphasizes the fetus's right to life as a natural right, legal positivism focuses on the certainty of written rules, while progressive law encourages responsiveness to social needs, particularly protecting women from the risks of illegal abortion. The perspectives of major religions in Indonesia generally reject abortion, although positive law provides limited exceptions for medical emergencies and pregnancies resulting from rape. Abortion regulation in Indonesia faces a normative dilemma as the law tends to be repressive while social reality demands greater protection for women. Regulatory reform that is more humanistic and progressive is needed, emphasizing balance between protecting the fetus's right to life and fulfilling women's rights to achieve substantive justice in accordance with Pancasila legal ideals and the constitution.